2007
DOI: 10.1038/sj.jhh.1002171
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise-induced nitric oxide production contributes to upregulation of circulating endothelial progenitor cells in healthy subjects

Abstract: Exercise has been proved to promote the number and activity of circulating endothelial progenitor cells (EPCs) in humans, which contributes to improvement in endothelial function and maintenance of cardiovascular homoeostasis. However, the mechanism underlying the effect of exercise on circulating EPCs in healthy subjects is not completely understood. Here, we investigated whether the regulation of acute exercise on circulating EPCs is associated with nitric oxide (NO), vascular endothelial growth factors (VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 33 publications
2
111
1
3
Order By: Relevance
“…Physical exercise has been shown to increase the function and number of circulating EPCs in healthy individuals (Hoetzer et al, 2007;Yang et al, 2007;Mö bius-Winkler et al, 2009;Walther et al, 2009;Witkowski et al, 2010), which is paralleled with improvement of endothelial function. However, it is not clear whether exercise contributes to the promotion of endothelial repair capacity of EPCs from elderly men and if yes, whether CXCR4 ⁄ JAK-2 signaling is involved in the functional regulation of EPCs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Physical exercise has been shown to increase the function and number of circulating EPCs in healthy individuals (Hoetzer et al, 2007;Yang et al, 2007;Mö bius-Winkler et al, 2009;Walther et al, 2009;Witkowski et al, 2010), which is paralleled with improvement of endothelial function. However, it is not clear whether exercise contributes to the promotion of endothelial repair capacity of EPCs from elderly men and if yes, whether CXCR4 ⁄ JAK-2 signaling is involved in the functional regulation of EPCs.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to favorably modifying traditional risk factors, physical exercise has been shown to prevent and restore age-associated loss in endothelial function in humans (DeSouza et al, 2000;Werner et al, 2009). Recent data also suggest that the beneficial effect of exercise on endothelial protection is, at least in part, related to the exercise-induced upregulation of EPC function and number (Laufs et al, 2004;Yang et al, 2007;Van Craenenbroeck et al, 2010;Witkowski et al, 2010). However, it is unclear whether physical exercise can improve in vivo reendothelialization capacity of EPCs from elderly men.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out above, several studies clearly demonstrated that an acute bout of exercise either in patients with CAD (2) or healthy subjects (58,86,94) resulted in the mobilization of EPCs from the BM. Along with the mobilization of EPCs, metabolic genes increase transiently after an acute bout and returning to near pre-exercise levels 24 h after the end of exercise (60,61).…”
Section: Single Exercise Bout Vs Exercise Training Programmentioning
confidence: 99%
“…and consequently, the proliferation of endothelial cells for the formation of new vessels [1][2][3][4] . Interestingly, the hypoxia and shear stress found in the skeletal musculature by the aerobic ET were described for being one of the most powerful physiological stimuli known for triggering the increase of the number and increasing the EPC function mediated by the synthesis of growth factors, especially the VEGF and nitric oxide (NO) 8,9,[13][14][15][16][17][18][19] . Hypoxia and shear stress alter the microvascular endothelium casing the EPC mobilization to these regions.…”
Section: Measurement Of the Citrate Synthase Enzyme Activitymentioning
confidence: 99%
“…Recent studies evidenced aerobic ET as responsible for promoting higher release and improving the bone-marrow derived EPC functional properties both in humans and animals, which contributes to the improvement of the endothelial function, angiogenesis and consequently, maintenance of cardiovascular homeostasis [13][14][15][16][17][18][19] . Although the ET effect on the EPC parameters has been evidenced, studies with alteration in the ET volume on the EPC and the capillarization have not been found yet.…”
Section: Introductionmentioning
confidence: 99%